Anti-inflammatory and antioxidative effects of Dan-Lou tablets in the treatment of coronary heart disease revealed by metabolomics integrated with molecular mechanism studies. (10th August 2019) - Li, Zhu; Yang, Liu; Liu, Yuechen; Xu, Huiyu; Wang, Shuo; Liu, Yijia; Zhao, Huan; Xie, Jing; Gao, Shan; Gao, Shuming; Xu, Yilan; Li, Lin; et al.
Abstract: Ethnopharmacological evidence: The Dan-Lou tablet (DLT), a well-known Chinese prescription, has definitive clinical efficacy in the treatment of precordial discomfort and pain caused by coronary heart disease (CHD). However, the pharmacological mechanism of DLT in the treatment of CHD has not been clearly elucidated and needs to be further explored. Aim of the study: We aimed to identify relevant biological pathways by assessing changes in biomarkers in response to DLT intervention in CHD to reveal the potential biological mechanism of DLT treatment for CHD. Materials and methods: The major chemical components in DLT were qualitatively analyzed using ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS), and a model of CHD in rats was subsequently established with a high-fat diet and left anterior coronary artery ligation (LADCA) followed by DLT intervention. Next, the metabolic profile of rat serum samples was analyzed using nontargeted metabolomics, wherein changes in the metabolites in serum samples before and after DLT administration were measured by PLS-DA, and two pathways of DLT treatment for CHD were predicted. Finally, predicted metabolomic pathways were verified by detecting and analyzing tissues from the rat model, revealing the mechanism of DLT in the treatment of CHD. Results: Forty-five major chemical components were identified by the chemical characterization of DLT. In terms of metabolism, 17 biomarkers of CHD in rats were identified. Among these biomarkers, linoleic acid, γ-linolenic acid and lysophosphatidylcholines (LPCs) were found to play an important role in energy metabolism and glycerophospholipid metabolism. Protein analysis revealed that EGFR phosphorylation was inhibited in CHD rats after DLT treatment, which lowered the expression of TNF-α, IL-6 and MMP9, decreased the expression levels of ox-LDL and MDA, and increased the expression of SOD. Conclusion: The mechanism of DLT in the treatment of CHD involves inhibiting the expression of EGFR and the activation of the MAPK signaling pathway by regulating glycerophospholipid metabolism (LPCs) and energy metabolism (linoleic acid and γ-linolenic acid). Therefore, inflammation-related (TNF-α, IL-6, MMP9) and oxidative stress-related (ox-LDL, MDA, SOD) indicators are affected, leading to the regulation of the oxidative stress state and anti-inflammatory effects. Graphical abstract: Image 1